2002
DOI: 10.1080/0307945021000024634
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the use of allopurinol to reduce plasma uric acid concentrations in the Red-tailed Hawk ( Buteo jamaicensis ) hyperuricaemic model

Abstract: The present paper reports the effects of allopurinol in a raptor hyperuricaemic model. The study was performed as a follow-up to previous experiments wherein allopurinol was used in doses of 100 and 50 mg/kg, and was proved to be toxic at these higher dose rates. To investigate whether 25 mg/kg (semel in die) s.i.d. allopurinol is a safe and effective dose in Red-tailed Hawks (Buteo jamaicensis) to reduce plasma uric acid concentrations, experimental studies were performed using the physiologically occurring p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…by food supplementation or brood size manipulation. As far as the first two methods are concerned, two recent studies on captive bird species showed that urate oxidase decreases the uric acid concentration more effectively than allopurinol (Poffers et al . 2002a,b).…”
Section: Adaptations To Oxidative Stressmentioning
confidence: 99%
“…by food supplementation or brood size manipulation. As far as the first two methods are concerned, two recent studies on captive bird species showed that urate oxidase decreases the uric acid concentration more effectively than allopurinol (Poffers et al . 2002a,b).…”
Section: Adaptations To Oxidative Stressmentioning
confidence: 99%
“…Although numerous reversed-phase chromatographic methods are used for analysis of oxypurines [11,[17][18][19][20][21], methylated purines [18,[22][23][24], 2,8-dihydroxyadenine [12,19,20], allopurinol and oxypurinol [11,[19][20][21]23,25], they are not designed to separate simultaneously all the purines specific for urinary calculi. Original double gradient of pH and methanol content in mobile phase was used, because we could not achieve satisfactory separation of all analytes with constant buffer pH.…”
Section: Methodological Aspects Of Extraction and Chromatographic Sepmentioning
confidence: 99%
“…Based on the lack of response at a dose of 25 mg/kg and the toxic effects at 50 mg/kg, allopurinol is not recommended in the red-tailed hawk. 27 It is unknown whether this finding should be extrapolated to psittacine birds.…”
Section: Xanthine Oxidase Inhibitorsmentioning
confidence: 99%